Stromal miR‐21 is more important than miR‐21 of tumour cells for the progression of gastric cancer. Issue 6 (2nd September 2014) - Uozaki, Hiroshi; Morita, Shigeki; Kumagai, Arisa; Aso, Tatsuya; Soejima, Yurie; Takahashi, Yoshihisa; Fukusato, Toshio
<x xml:space="preserve">Abstract</x> Background Gastric cancer (GC) is a common cancer globally. miRNA‐21 (miR‐21) appears to be important in the tumourigenesis of almost all types of human cancer. However its precise localization in GC has yet to be clarified. We thus examined miR‐21 localization in GC and revealed its clinicopathological importance. Methods Tissue arrays of 469 GCs from 454 patients were examined for miR‐21 using in situ hybridization (ISH). The positivity was evaluated separately in tumour cells and stromal cells. Conventional sections of 10 GCs were also stained. Eight cases were examined by quantitative RT‐PCR (qRT‐PCR). Results miR‐21 was highly expressed in tumour cells of 44% of cases and in cancer stroma of 51% of cases. miR‐21 of tumour cells was not related to clinicopathological factors, whereas stromal miR‐21 was related to many factors including tumour stage, size, and nodal metastasis. Stromal miR‐21 gradually increased during tumour progression. ISH of whole sections showed stronger stromal positivity in invasive areas with desmoplastic reaction. Cancer stroma also showed higher miR‐21 expression than tumour and non‐tumourous tissue in the qRT‐PCR study. Conclusion Stromal miR‐21 is closely related to tumour progression in GC. Stromal miR‐21 of tumours might be a target of treatment.